Multi-objective-optimization of process parameters of diesel engine fueled with biodiesel/2-ethylhexyl nitrate by using Taguchi method. (15th September 2021) - Simsek, Suleyman; Uslu, Samet; Simsek, Hatice; Uslu, Gonca
Abstract: In this investigation, the effects of fuel mixtures prepared using different proportions of biodiesel (99.5%, 98.5% & 97.5%) and 2-ethylhexyl nitrate (EHN) (0.5%, 1.5% & 2.5%) on the performance and emission characteristics of diesel engine were investigated at different loads (2000, 2500 & 3000 W). Experiments were designed using Taguchi with L27 orthogonal array (OA), and the load, % blends of EHN and % blends of biodiesel with three levels of each were taken as control parameters. Also, optimization has been performed to obtain the best combination of control parameters to optimize the response characteristics such as brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOx ), and smoke. Optimization analysis revealed that biodiesel ratio of 99.2%, EHN ratio of 1.3%, and the load of 2300 W were the optimum results for the best performance and emission values. The optimum responses according to the optimum parameters determined as 25.05%, 781.248 g/kWh, 0.085%, 20.30 ppm, 632.72 ppm, and 0.257% for BTE, BSFC, CO, HC, NOx, and smoke, respectively. The maximum error of 9.42% obtained from the validation between the optimization results and the experimental results reveals that the findings of this investigation are acceptable. Highlights: Taguchi design was applied to find the optimum diesel engine running parameters for best engine responses. EHN ratio, biodiesel ratio, and load have been chosen as affecting factors to engine outcomes. Proposed Taguchi model is capable for mapping engine outcome paradigms by high accuracy.